Retail and place attractiveness: The effects of big-box entry on property values - Sven-Olov Daunfeldt; Oana Mihaescu; Özge Öner; Niklas Rudholm (Research Institute of Industrial Economics (IFN), 2019)
Opponents of big-box entry argue that large retail establishments generate noise and other types of pollution and a variety of negative externalities associated with traffic. Big-box advocates, on the other hand, argue that access to a large retail market delivers not only direct economic benefits but also a variety of positive spillover effects and therefore can be considered a consumer amenity that increases the attractiveness of the entry location. To test the validity of these competing arguments, we use the entry of IKEA in Sweden as a quasi-experiment and empirically investigate whether increased access to retail affects place attractiveness, which is proxied by residential property values. We find that IKEA entry increases the prices of the properties sold in the entry cities by, on average, 4.4% or 60,425 SEK (approximately 6,400 USD), but this effect is statistically insignificant for the properties in the immediate vicinity of the new IKEA retail trade area. In addition, we observe an attenuation of the effect with distance from the new IKEA store and the associated retail trade area, where the properties located 10 km away experience a 2% price increase. Our results are in line with some previous findings regarding the effects of entry by Walmart or supermarket stores in the US and show that large retailers have the potential to increase place attractiveness, but perhaps not in the immediate vicinity of the new establishment.
Keywords: D22; P25; R12; R32; 330; Retail trade; Large retailers; Property values; Place attractiveness; Difference-in-differences estimation